Geology and geomorphology as support for territorial and environmental management in Brazil - Cordeiro de Moura, Joao; Claudino-Sales, Vanda; Martins de Moura-Fe, Marcelo (Investigaciones Geográficas: Una mirada desde el sur, 2024)
The physical environment has been increasingly exploited due to the expansion of economic activities in the territories, which requires an increasingly intense use of natural resources. These activities sometimes disregard the characteristics of natural components, causing degradation. In the municipality of Viçosa do Ceará, in the northwestern region of Ceará, northeastern Brazil, geomorphological features and geological formations stand out as elements of the local physical environment that have a high geotouristic, scientific and scenic potential, among others, which, in some contexts, are exploited without proper understanding of their specificities, thus causing negative environmental impacts. With this in mind, this article aims to characterize and analyze the geological-geomorphological aspects of the municipality of Viçosa do Ceará as support for territorial and environmental management. The methodology used in this research, based in a systemic approach, was organized into three main stages: a survey of the theoretical framework, fieldwork and systematization of the characterization of the natural components using geoprocessing techniques. The study showed that the municipality of Viçosa do Ceará has a rich geological and geomorphological diversity, which requires land-use planning and environmental management policies that consider the potential and limitations of these components of the physical environment.